Anxiety, Insomnia and Somatoform Disorders in University Students of Punjab: A Cross-Sectional Study - Mahmood-ul-Hassan, Ameer Hamza; Hassaan Khan, Muhammad; Nooz, Nehala; Tahir, Muhammad Amaz; Sannan, Abdul; Usman Ali, Muhammad (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Somatoform disorders, Anxiety, and Insomnia have a very noticeable prevalence among the general population. All these conditions overlap in different settings and conditions. They can cause a constant state of morbidity and can decrease the response to certain treatments in different patients. Objectives: Because, little or no research has been done on the relationship between somatoform disorders, anxiety, and Insomnia. Therefore, this study aimed to find the prevalence of somatoform disorders, Anxiety, and Insomnia in a specific population of university students in Punjab and find their relationship with each other. Methods: 849 enrolled students from different universities were reached online to fill in a self-administered questionnaire. All subjects were assessed and evaluated via Patient Health Questionnaire-15(PHQ-15), Hamilton Anxiety Rating Scale (HAM-A), and Insomnia Severity Index (ISI). Regression Analysis was done. Results: Out of 849 subjects,304 were males, and 545 were Females. Our study found that female subjects had a high prevalence of Somatization, Anxiety, and Insomnia. Moreover, these disorders were more prevalent in certain groups than in others. These groups include those females who live in hostels away from their homes for their university studies. Conclusion: The study warrants further research on a bigger and general population. Also, it encourages the health care providers to have a different approach to patients in general health care settings. With proper screening and a systematic approach, effective diagnosis, and treatment of not only one but three concurring diseases are possible.